2008
DOI: 10.1016/j.cub.2008.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Regulation of nanos Is Required for Its Function in Dendrite Morphogenesis

Abstract: Spatial control of mRNA translation can generate cellular asymmetries and functional specialization of polarized cells like neurons. A requirement for the translational repressor Nanos (Nos) in the Drosophila larval peripheral nervous system (PNS) implicates translational control in dendrite morphogenesis [1]. Nos was first identified by its requirement in the posterior of the early embryo for abdomen formation [2]. Nos synthesis is targeted to the posterior pole of the oocyte and early embryo through translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 35 publications
2
83
0
Order By: Relevance
“…Second, it is crucial for germ cell development, where it mediates self-renewal of germ stem cells, their migration to the gonads, and suppresses somatic fate and premature differentiation (Hayashi et al, 2004). Finally, Nanos fulfils some functions in the nervous system of Drosophila (Ye et al, 2004;Brechbiel and Gavis, 2008). Nanos expression patterns in various animals are consistent with these functions.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Second, it is crucial for germ cell development, where it mediates self-renewal of germ stem cells, their migration to the gonads, and suppresses somatic fate and premature differentiation (Hayashi et al, 2004). Finally, Nanos fulfils some functions in the nervous system of Drosophila (Ye et al, 2004;Brechbiel and Gavis, 2008). Nanos expression patterns in various animals are consistent with these functions.…”
Section: Introductionmentioning
confidence: 85%
“…Lastly, the function of Nanos in the nervous system is by far the least well studied. Work done in Drosophila has shown that Nanos is required for dendrite morphogenesis (Ye et al, 2004;Brechbiel and Gavis, 2008) through an unclear mechanism. In the mouse, Nanos1 is expressed in the central nervous system, but its function is unidentified (Haraguchi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The system was adapted for transgenic use in Drosophila to investigate nos mRNA localization in late oocytes (Forrest and Gavis, 2003), and has been subsequently applied to grk, bcd and osk (Jaramillo et al, 2008;Weil et al, 2006;Zimyanin et al, 2008) (Fig. 1C-F), as well as to several neuronal mRNAs (Ashraf et al, 2006;Brechbiel and Gavis, 2008;Estes et al, 2008). A major strength of this system is the production of fluorescent transcripts, at or near physiological levels, that have been subject to endogenous processing steps.…”
Section: Box 1 Key Examples Of Localized Mrnasmentioning
confidence: 99%
“…Many groups have routinely assessed RNA localization by in situ hybridization (ISH) in either cultured dissociated neurons or in brain slices. Recently, novel methods have been developed to directly visualize individual dendritic RNAs [e.g., microinjection of fluorescently labeled RNAs in living hippocampal neurons (Shan et al, 2003;Gao et al, 2008) and the MS2 system (Brechbiel and Gavis, 2008;Dictenberg et al, 2008)]. The first two mentioned studies focused on the molecular mechanism of dendritic RNA localization; the latter studied the kinetics of RNA transport in living neurons.…”
Section: Introductionmentioning
confidence: 99%